Effect of skill level on knee flexor and extensor strength in male judo - Zhou, J.; Jiang, Y.; Liu, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Judo has a high requirement of the physical strength of lower limb. In this paper, the centripetal knee force of national master athletes and first-grade athletes of male Judoka was measured using the ISOMED2000 Isokinetic system. Try to discuss the differences between different grades of judoka in the area of the physical strength of lower limb. Judo-related specific knee strength indices, such as peak torque in relation to body weight, flexor torque in relation to the extensor torque and average power of knee, were compared between the two groups by statistic analysis. The results showed that the first-grade athletes did not significantly differ from the national master athletes in terms of relative power of the knee flexors, but significant difference existed in the absolute power and explosive strength of the knee extensors between the two levels of athletes.